Current Research on Zinc Oxide Nanoparticles: Synthesis, Characterization, and Biomedical Applications - Ashok Kumar Mandal; Saurav Katuwal; Felix Tettey; Aakash Gupta; Salyan Bhattarai; Shankar Jaisi; Devi Prasad Bhandari; Ajay Kumar Shah; Narayan Bhattarai; Niranjan Parajuli (Nanomaterials, 2022)
Zinc oxide nanoparticles (ZnO-NPs) have piqued the curiosity of researchers all over the world due to their extensive biological activity. They are less toxic and biodegradable with the capacity to greatly boost pharmacophore bioactivity. ZnO-NPs are the most extensively used metal oxide nanoparticles in electronic and optoelectronics because of their distinctive optical and chemical properties which can be readily modified by altering the morphology and the wide bandgap. The biosynthesis of nanoparticles using extracts of therapeutic plants, fungi, bacteria, algae, etc., improves their stability and biocompatibility in many biological settings, and its biofabrication alters its physiochemical behavior, contributing to biological potency. As such, ZnO-NPs can be used as an effective nanocarrier for conventional drugs due to their cost-effectiveness and benefits of being biodegradable and biocompatible. This article covers a comprehensive review of different synthesis approaches of ZnO-NPs including physical, chemical, biochemical, and green synthesis techniques, and also emphasizes their biopotency through antibacterial, antifungal, anticancer, anti-inflammatory, antidiabetic, antioxidant, antiviral, wound healing, and cardioprotective activity. Green synthesis from plants, bacteria, and fungus is given special attention, with a particular emphasis on extraction techniques, precursors used for the synthesis and reaction conditions, characterization techniques, and surface morphology of the particles.